2014
DOI: 10.14737/journal.jahp/2014/2.3.33.37
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Prevalence and Risk Factors of Brucellosis in Cattle and Buffaloes in District Hyderabad, Pakistan

Abstract: Brucellosis is recognized worldwide as an important bacterial disease of cattle, buffaloes, goats etc, that causes infertility in both male and female animals. The present study was carried out to determine the prevalence of brucellosis in aborted cattle and buffaloes in district Hyderabad, Sindh, Pakistan. Amongst 69 and 89 milk samples of cattle and buffaloes, the positive reactors for Brucella abortus antibodies examined by milk ring test (MRT) were, 22 (31.88%) and 42 (47.19%), respectively. The main const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…We have used this test in our study and found 14% cases as positive. This prevalence is quite low as compared to our study in Hyderabad (Soomro et al, 2014) that showed 31-47% prevalence in cattle and buffaloes respectively. Likewise, in another study in Faisalabad, 20.1% was recorded in horses (Gul et al, 2013).…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…We have used this test in our study and found 14% cases as positive. This prevalence is quite low as compared to our study in Hyderabad (Soomro et al, 2014) that showed 31-47% prevalence in cattle and buffaloes respectively. Likewise, in another study in Faisalabad, 20.1% was recorded in horses (Gul et al, 2013).…”
Section: Discussioncontrasting
confidence: 73%
“…This reflects the better managemental and sanitary conditions in dairy farms of Karachi as compared to other small cities of Pakistan. Because, it is well recognized that sanitary conditions like disposal of aborted material, contact with stray dogs and other wild animals etc., are the major risk factors for brucellosis (Soomro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It's may be due to lack of information. There was no proper disposal of the aborted material at farms in district Hyderabad (Soomro et al, 2014).There were no proper fences or boundary wall around the farm. Rodents and dogs were also present at the farm.…”
mentioning
confidence: 99%